Pathogenicity and rapid growth kinetics of feline immunodeficiency virus are linked to 3' elements. - Jesse Thompson; Martha MacMillan; Karen Boegler; Charles Wood; John H Elder; Sue VandeWoude (PLoS ONE, 2011)
Chimeric viruses constructed between a highly pathogenic Feline Immunodeficiency Virus isolate (FIV-C36) and a less pathogenic but neurotropic strain (FIV-PPR) have been used to map viral genetic determinants of in vivo pathogenicity. Chimeric virus FIV-PCenv, which contains FIV-C36 genome from the 3' region of pol to upstream of the 3'LTR on an FIV-PPR backbone, was previously shown to be replication-competent in vivo, inducing altered CD4(+) T-cell and neutrophil profiles intermediate between parental strains following a delay in viral replication during initial infection. Examination of FIV-PCenv proviral sequences recovered at week 11 post-infection revealed two changes compared to initial viral inoculum; the most significant being arginine to histidine in the integrase region of Pol at residue 813 (R813H). Pooled plasma from the initial in vivo study was used to inoculate a second cohort of cats to determine whether similar virulence and kinetics could be established following primary infection. Viral replication kinetics and immunocyte profiles were monitored in blood, bone marrow, and saliva over a one-year period. Passaged FIV-PCenv again displayed intermediate phenotype between parental strains, but unlike primary experiments, the onset of acute viremia was not delayed. CD4/8 alterations were noted in all groups of animals, though significant changes from controls were delayed in FIV-PPR infected animals compared to FIV-C36 and FIV-PCenv. In vivo passage of FIV-PCenv increased replication-competence relative to the initial molecularly-cloned chimera in association with one adaptive nucleotide change in the 5' end of the genome relative to primary tissue culture inoculum, while mutations in the 3' end of the genome were not detected. The results are consistent with the interpretation that 3' elements contribute to heightened virulence of FIV-C36, and that integrase residue 813 plays an important role in facilitating successful in vivo replication.